2013
DOI: 10.1177/1470320313494432
|View full text |Cite
|
Sign up to set email alerts
|

The angiotensin-converting enzyme (ACE) I/D polymorphism in Parkinson’s disease

Abstract: Objective: The angiotensin-converting enzyme (ACE) may be involved in the pathogenesis of Parkinson's disease (PD). There have been several studies investigating the association between ACE gene I/D polymorphism and PD risk, but they reported inconsistent findings. We performed a meta-analysis to investigate the association between ACE gene I/D polymorphism and PD risk. Methods: Published literature from PubMed and Embase databases were searched for eligible publications. Pooled odds ratios (ORs) with 95% conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The results were independent of the presence of hypertension, hyperlipemia, stroke, or smoking. However, other studies reported no such association in non-Chinese PD patients and controls [69,75].…”
Section: Alterations Of the Ras Pathway In Pd Patientsmentioning
confidence: 88%
“…The results were independent of the presence of hypertension, hyperlipemia, stroke, or smoking. However, other studies reported no such association in non-Chinese PD patients and controls [69,75].…”
Section: Alterations Of the Ras Pathway In Pd Patientsmentioning
confidence: 88%
“…To date, meta-analyses on human subjects have not provided explicit evidence for the association between ACE gene I/D polymorphism and PD risk [259].…”
Section: Ras In Parkinson's Disease and Tardive Dyskinesiamentioning
confidence: 99%
“…Circulating Ang II is generated from Ang I by ACE carboxypeptidase activity in the pulmonary endothelial cells (Herichova and Szantoova, 2013;Su et al, 2015), and its effects are mediated mainly via AT1R receptors. The RAS axis is of scientific, medical, and pharmacological interest owing to its effects on blood pressure and heart hypertrophy (Herichova and Szantoova, 2013) (Figure 1).…”
Section: General Organization Of the Renin-angiotensin Systemmentioning
confidence: 99%